TP53 codon 72 polymorphism as a risk factor for cardiovascular disease in a Brazilian population - M.A.C. Smith; M.D.A. Silva; M.S. Cendoroglo; L.R. Ramos; L.M.Q. Araujo; R.W. Labio; R.R. Burbano; E.S. Chen; S.L.M. Payão (Brazilian Journal of Medical and Biological Research, 2007)
TP53, a tumor suppressor gene, has a critical role in cell cycle, apoptosis and cell senescence and participates in many crucial physiological and pathological processes. Identification of TP53 polymorphism in older people and age-related diseases may provide an understanding of its physiology and pathophysiological role as well as risk factors for complex diseases. TP53 codon 72 (TP53:72) polymorphism was investigated in 383 individuals aged 66 to 97 years in a cohort from a Brazilian Elderly Longitudinal Study. We investigated allele frequency, genotype distribution and allele association with morbidities such as cardiovascular disease, type II diabetes, obesity, neoplasia, low cognitive level (dementia), and depression. We also determined the association of this polymorphism with serum lipid fractions and urea, creatinine, albumin, fasting glucose, and glycated hemoglobin levels. DNA was isolated from blood cells, amplified by PCR using sense 5'-TTGCCGTCCCAAGCAATGGATGA-3' and antisense 5'-TCTGGGAAGGGACAGAAGATGAC-3' primers and digested with the BstUI enzyme. This polymorphism is within exon 4 at nucleotide residue 347. Descriptive statistics, logistic regression analysis and Student t-test using the multiple comparison test were used. Allele frequencies, R (Arg) = 0.69 and P (Pro) = 0.31, were similar to other populations. Genotype distributions were within Hardy-Weinberg equilibrium. This polymorphism did not show significant association with any age-related disease or serum variables. However, R allele carriers showed lower HDL levels and a higher frequency of cardiovascular disease than P allele subjects. These findings may help to elucidate the physiopathological role of TP53:72 polymorphism in Brazilian elderly people.